Dynamical Anisotropic Dark Energy Cosmological Model in General Relativity. Issue 1 (2nd January 2019) - Reddy, D.R.K.; Aditya, Y.; Ramesh, G.
ABSTRACT: We have investigated an anisotropic dark energy cosmological model in the presence of anisotropic dark energy fluid coupled with mass less scalar field in KantowskiSachs space-time in general theory of relativity. A physically viable dark energy cosmological model is presented using (i) a hybrid expansion law proposed by Akarsu et al. (JCAP. 01, 022: 2014) and (ii) a relation between the metric potential. The dark energy density, the equation of state (EoS) parameter and the skewness parameters of the model are determined and their physical siguificance is pointed out. The deceleration parameter and the jerk parameter of the model show that there is a smooth transition of the uuiverse from early deceleration to late time acceleration which confirms the observations modem cosmology.